Saline Load Test for Detecting Traumatic Arthrotomy in the Wrist - Goyal, Nitin; Bohl, Daniel D.; Frank, Rachel M.; Slikker, William, III; Fernandez, John J.; Cohen, Mark S.; Wysocki, Robert W. (Journal of Wrist Surgery, 2019)
Background Open injuries communicating with the wrist joint are essential to detect to facilitate timely, appropriate treatment. While the saline load test to detect traumatic arthrotomy has been well studied in the knee and ankle, it has not been studied in the wrist, and therefore the appropriate volume of saline infusion to detect traumatic arthrotomy is not known.Purpose The purpose of this study was to utilize wrist arthroscopy to determine the saline infusion volume necessary to achieve 99% sensitivity in detecting traumatic arthrotomy.Methods Twenty consecutive patients undergoing elective wrist arthroscopy were prospectively enrolled. A 5-mm arthrotomy was established between the third and fourth dorsal extensor compartments. An 18-gauge needle was inserted into the 6R portal on the radial side of the extensor carpi ulnaris. Sterile normal saline was injected into the wrist joint through the needle at a rate of 0.1 mL per second until extravasation from the 3–4 portal was visualized. Saline volumes required for extravasation were analyzed.Results The mean saline volume required for extravasation was 0.8 mL. The volume of saline needed to achieve sensitivities of 50, 90, 95, and 99% were 0.4, 2.2, 2.3, and 2.5 mL respectively.Conclusions The saline infusion volume required to detect a dorsal radiocarpal arthrotomy with 99% sensitivity was 2.5 mL. We recommend using at least 2.5 mL when performing the saline load test to rule out a potential arthrotomy to the wrist in the traumatic setting.Level of Evidence: This is a Level II, diagnostic study.
Keywords: arthrotomy; saline load test; wrist